Relawan Pajak 2021: Upaya Menjaga Kepatuhan Wajib Pajak melalui Pendampingan Pengisian SPT secara Daring - Rahadi Nugroho; Nur Farida Liyana; Hanik Susilawati Muamarah; Suparna Wijaya (Jurnal Nusantara Mengabdi, 2022)
Purpose: The purpose of this program is to support Pondok Aren Tax Office in increasing tax compliance of individual tax payer by assisting tax payer fulfilling their income tax return in online platform. Method: This program assisted individual tax payer to fulfill income tax return of 2020 fiscal year. This program was conducted from 1-31 March 2021 employing 269 students and 28 lecturers of PKN STAN. They were divided into 11 team and assigned for two days. The activity mostly utilized Whatsapp application. Result: 436 individual tax payers joined this program. 255 successfully submitted tax return although 181 tax payers eventually could not join this program due to personal reasons. Surprisingly, tax compliance increased by 20% compared to last year. Conclusion: This program is considered successful in assisting individual tax payer fulfilling income tax return by online platform. Since this program is the first experience of PKN STAN and DG Tax, the obstruction during this program might become valuable in conducting the same program in the following year. Soft-skill training could be carried out by a trainer.